Techniques to resect the distal ureter in robotic/laparoscopic nephroureterectomy - Weil R. Lai; Benjamin R. Lee (Asian Journal of Urology)
Treatment of clinically-organ confined high grade urothelial carcinoma of the upper tract has historically comprised open nephroureterectomy, with the distal ureter and bladder cuff mobilized through a separate open pelvic incision. To decrease morbidity, urologists have increasingly adopted laparoscopy and robotics in performing nephroureterectomy. In many published series of laparoscopic nephroureterectomy, the distal ureter and bladder cuff are detached from the bladder endoscopically by a variation of the “pluck” technique, with the resulting bladder defect left to heal by prolonged indwelling urethral catheter drainage. While the distal ureter and bladder cuff can be excised laparoscopically, it does require advanced laparoscopic skills. With the wrist articulation and stereoscopic vision in robotic surgery, robotic nephroureterectomy (RNU) and bladder cuff excision can be performed in antegrade fashion to mimic the open technique together with the ability to intracorporeally close the bladder defect in a watertight, mucosa to mucosa fashion after excising the bladder cuff. In this review, we discuss the published minimally invasive techniques in resecting the distal ureter and bladder cuff during laparoscopic and RNU. Keywords: Transitional cell carcinoma, Robotic nephroureterectomy, Laparoscopy, Robotic surgical procedures, Ureteral neoplasms